A Jal Neti: A Public Hygiene in Covid-19 - Swaranjali, Jangde; Anita, Sharma (International Research Journal of Ayurveda & Yoga, 2020)
Corona virus disease 2019 is an infectious disease caused by a newly discovered corona virus. most people infected with the covid-19 virus will experience mild to moderate respiratory illness and recover without special treatment, while co morbid patients are more likely to develop serious illness. The best way to prevent its spread is to be well informed in general public. The virus spreads primarily through droplets or discharge from infected person. The nose and mouth represents entry portals for the covid 19 and also it is the place where viral load is highest. Many systemic medications, treatments and measures have been proposed. Neti karma mentioned as a shatkarma in yoga as a way of body cleansing from toxins can be and additional measures for the current public health to reduce the viral load in nasal cavities and may prevent and control this pandemic.